2020
DOI: 10.1002/chem.202003097
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids with More than One Metal: Optical and Electrochemical Properties versus d‐Block Metal Combinations

Abstract: Thirteen N-butylpyridinium salts, including three monometallic [C 4 Py] 2 [MCl 4 ], nine bimetallic [C 4 Py] 2 [M 1Àx a M x b Cl 4 ]a nd one trimetallicc ompound [C 4 Py] 2 [M 1Ày-z a M y b M z c Cl 4 ](M = Co, Cu, Mn; x = 0.25, 0.50 or 0.75 and y = z = 0.33), were synthesized and their structure and thermala nd electrochemical properties were studied. All compoundsa re ionic liquids(ILs) with melting points between 69 and 93 8C. X-ray diffraction provest hat all ILs are isostructural. The conductivity at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(51 citation statements)
references
References 80 publications
10
40
1
Order By: Relevance
“…While the intensity of the reflections differs to some extent, which is probably due a high number of defects and disorder in each sample, the position of the reflections are identical. As with previously published data on chloridecontaining MILs, [42] the background of the patterns is relatively noisy.…”
Section: Hydrogen Bonds Dà Hsupporting
confidence: 73%
See 2 more Smart Citations
“…While the intensity of the reflections differs to some extent, which is probably due a high number of defects and disorder in each sample, the position of the reflections are identical. As with previously published data on chloridecontaining MILs, [42] the background of the patterns is relatively noisy.…”
Section: Hydrogen Bonds Dà Hsupporting
confidence: 73%
“…Additionally, it is important to keep in mind that the starting point for the DFT calculations was the previously published copper-chloride-containing MIL, which possesses a different albeit isostructural and isoelectronic anion. 42 This also shows the transferability of the method from better-known compounds to lesser known structures.…”
Section: Hydrogen Bonds Dà Hmentioning
confidence: 84%
See 1 more Smart Citation
“…[114,215] While this concept is just being established, we have recently demonstrated that a wide variety of ILPs with different metal/metal ratios and various metal/metal combinations are accessible. [216] Clearly, following the concept recently demonstrated, these and other ILPs are attractive for the formation of (metal sulfide) nanoparticles with a highly flexible and potentially quite unusual composition. [114] Similar observations can also be made for the sulfur sources, not only for metal containing ILs.…”
Section: Future Perspectives and Challengesmentioning
confidence: 95%
“…This is particularly interesting when considering the synthesis of compounds with more complex compositions: suitable ILPs can be made to contain all metal ions needed for product formation and thus possibly also provide access to non‐stoichiometric compounds that are not easily accessible otherwise [114,215] . While this concept is just being established, we have recently demonstrated that a wide variety of ILPs with different metal/metal ratios and various metal/metal combinations are accessible [216] . Clearly, following the concept recently demonstrated, these and other ILPs are attractive for the formation of (metal sulfide) nanoparticles with a highly flexible and potentially quite unusual composition [114] …”
Section: Future Perspectives and Challengesmentioning
confidence: 99%